2016
DOI: 10.1186/s40064-016-2712-5
|View full text |Cite
|
Sign up to set email alerts
|

Determinants for the success of regional ICT ventures: a close examination of South Korea

Abstract: BackgroundThis study identifies the key motivational factors in enhancing economic performance and increasing new job opportunities for information and communication technology ventures (ICTVs) in South Korea and examines their potential causal relationships through structural equation modeling analysis on data collected from over 200 ICTVs located in Daedeok Innopolis.ResultsThe results indicate that the economic performance of ICTVs is determined mainly by government support, innovation effort, and private e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 60 publications
1
8
0
Order By: Relevance
“…Fourth, GSFI has a significant positive effect on firm innovation, confirming the relationship reported in the literature (Alguezaui and Filieri, 2010;Chapman and Hewitt-Dundas, 2018;Dumont, 2017;Kang and Park, 2012;Mustar and Lar edo, 2002;Wei and Liu, 2015;Yes ¸il and Do gan, 2019). Furthermore, GSFI significantly positively affects firm performance, consistent with prior studies (Alkahtani et al, 2020;Fajnzylber et al, 2009;Park et al, 2016). These previous studies proved that government incentives not only enhance sustainable competitive performance in emerging economies but also greatly improve innovation capacity in both developed and developing countries.…”
Section: Mediation Effectssupporting
confidence: 87%
See 4 more Smart Citations
“…Fourth, GSFI has a significant positive effect on firm innovation, confirming the relationship reported in the literature (Alguezaui and Filieri, 2010;Chapman and Hewitt-Dundas, 2018;Dumont, 2017;Kang and Park, 2012;Mustar and Lar edo, 2002;Wei and Liu, 2015;Yes ¸il and Do gan, 2019). Furthermore, GSFI significantly positively affects firm performance, consistent with prior studies (Alkahtani et al, 2020;Fajnzylber et al, 2009;Park et al, 2016). These previous studies proved that government incentives not only enhance sustainable competitive performance in emerging economies but also greatly improve innovation capacity in both developed and developing countries.…”
Section: Mediation Effectssupporting
confidence: 87%
“…Governments encourage innovative activities through tax breaks, loans, social assistance, and financial assistance, among other measures. On the basis of a systematic review, Jugend et al (2020) identified four types of government support for innovation: (1) financial support for R&D activities, with 38 articles, two of which used primary data (Spanos et al, 2015;Wanzenb€ ock et al, 2013); (2) development through innovation, with 39 articles, four of which used primary data (Joo and Suh, 2017;Park et al, 2016;S a and Pinho, 2019;Songling et al, 2018); (3) support for sectorial programs, with 14 articles, one of which used primary data (Zailani et al, 2019); and (4) university-industry-government collaboration, with 12 articles, three of which used primary data (Hewitt-Dundas and Roper, 2018;Jugend et al, 2018;Kang and Park, 2012).…”
Section: Government Support For Innovationmentioning
confidence: 99%
See 3 more Smart Citations